2018
DOI: 10.1177/0004867418815987
|View full text |Cite
|
Sign up to set email alerts
|

Thirty-year cardiovascular risk score in patients with newly diagnosed bipolar disorder and their unaffected first-degree relatives

Abstract: Objectives: Bipolar disorder is associated with a decreased life expectancy of 8–12 years. Cardiovascular disease is the leading cause of excess mortality. For the first time, we investigated the Framingham 30-year risk score of cardiovascular disease in patients with newly diagnosed/first-episode bipolar disorder, their unaffected first-degree relatives and healthy individuals. Methods: In a cross-sectional study, we compared the Framingham 30-year risk score of cardiovascular disease in 221 patients with new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 44 publications
(54 reference statements)
2
15
0
Order By: Relevance
“…Several studies found lower blood pressure values in patients with schizophrenia and bipolar disorders compared with general population samples [4,31,32]. In the most recent Danish study, the authors argued that the finding was surprising, since subjects in their healthy comparison group were blood donors and likely with a healthy lifestyle [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies found lower blood pressure values in patients with schizophrenia and bipolar disorders compared with general population samples [4,31,32]. In the most recent Danish study, the authors argued that the finding was surprising, since subjects in their healthy comparison group were blood donors and likely with a healthy lifestyle [32].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies found lower blood pressure values in patients with schizophrenia and bipolar disorders compared with general population samples [4,31,32]. In the most recent Danish study, the authors argued that the finding was surprising, since subjects in their healthy comparison group were blood donors and likely with a healthy lifestyle [32]. A tentative explanation may reside in the use of hypotensive medications: either first or second-generation antipsychotics, particularly chlorpromazine, clozapine or quetiapine, are associated with reduced blood pressure and orthostatic hypotension [33].…”
Section: Discussionmentioning
confidence: 99%
“…Further, in mood disorders there is a heightened prevalence of cooccurring medical conditions such as obesity, diabetes and cardiovascular disease (Coello et al, 2019;Dalack and Roose, 1990;Goldstein et al, 2020;Mansur et al, 2019). These have been linked to a more severe coronavirus 2 (SARS-CoV-2) manifestation (Zaman et al, 2020), and may amplify psychological distress by increasing a patient's worries about the heightened personal risk of infection-related mortality or poor long-term health outcomes (Goldstein, 2017;Mansur et al, 2015;Zaman et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, BPD failed to show any differences compared to control participants. Recent evidence suggests a genetic component to CVD in BD, with a higher prevalence of cardiovascular risk factors and increased Framingham risk score present among unaffected siblings/first-degree relatives of individuals with BD (Tsao et al 2019 ; Coello et al 2019 b). Furthermore, several overlapping pleiotropic genes have been implicated with both CVD and BD (Amare et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%